Implementation of Madrasah Principal Leadership and Teacher Professionalism Level in Improving the Quality of Graduates - Yurnadewi, Yurnadewi; Nasor, M.; Hidayah, Nur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to describe and analyze the implementation of madrasah principal leadership in developing teacher professionalism, the level of teacher professionalism in carrying out professional duties, and its implications for graduate quality at MAN 1 Bandar Lampung, MAN 1 Pesawaran, and MAN 1 Pringsewu. This research employed a qualitative approach using a multisite study design. The data in this study consist of qualitative data on madrasah principal leadership, teacher professionalism, and graduate quality. The data sources include primary data from madrasa principals and teachers, as well as secondary data from official madrasa documents. Data were collected through observation, in-depth interviews, and document analysis, while data analysis was conducted through data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings reveal that madrasa principals play a strategic and multifaceted leadership role by regularly planning, organizing, implementing, and evaluating continuous teacher professional development programs. Differences in leadership focus were identified across sites, such as technology-based supervision, mentoring for new teachers, and innovation-oriented instructional leadership, reflecting contextual adaptation to institutional needs. Teacher professionalism is demonstrated through strong pedagogical competence, mastery of subject matter, effective classroom management, social engagement, and exemplary personal character, all of which contribute to effective learning environments and positive student development. The study further shows that the synergy between madrasah principal leadership and teacher professionalism significantly enhances graduate quality, not only in terms of academic achievement but also in non-academic skills, religious character, creativity, and competitiveness for higher education and social participation. This study concludes that the integrated relationship between effective madrasah principal leadership and sustained teacher professionalism is a key determinant in producing high-quality, holistic, and adaptive madrasah graduates capable of meeting contemporary educational challenges.